Impact of shipping alliances on the competitiveness of the top busiest ports : port of Hong Kong vs port of Shenzhen - Yeo, Jun Yang (2016)
The liner shipping market has witnessed increasing market consolidation through shipping alliances. This paper evaluates the impacts of shipping alliances on the competitiveness of the ports of Hong Kong and Shenzhen. Primary research findings revealed the decision making criteria for port choice selection namely: ‘Geographical Location’, ‘Port Connectivity’, ‘Port Reliability’ and ‘Preference of Shipping Line’s Clients/ Shippers’. Secondary research utilized ‘Porter’s Diamond Model’ to compare the competitiveness between Port of Hong Kong and Port of Shenzhen. The results show that the Port of Shenzhen enjoys competitive advantage over the Port of Hong Kong. The specific research interest on shipping alliances’ impacts will shed light on what decision makers in port authorities can do to help the ports achieve better competitiveness.